Probing the interaction of iron complex containing N3S2 macrocyclic ligand with bovine serum albumin using spectroscopic techniques - El-Shamy, Hany; Shaban, Shaban Y.; El-Mehasseb, Ibrahim; El-Kemary, Maged; van Eldik, Rudi (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2019)
The interaction of bovine serum albumin (BSA) with seven-coordination iron (II) complex containing sulfur-based macrocyclic ligand was investigated by means of UV/vis absorption spectroscopy and fluorescence quenching technique. The accurate fluorescence spectra are obtained by using Inner filter effect (IFE) correction. The apparent association constant, kapp, the number of binding sites, n, and the apparent binding constant KSV were found to be 0.95 × 103 M− 1, 0.96, and 6.13 × 104 M−1, respectively. It found that BSA molecules are adsorbed on the surface of iron (II) complex by electrostatic interaction. The quenching mechanism is discussed involving energy transfer from BSA to iron (II) complex.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Bovine serum albumin; Energy transfer; Fluorescence quenching; Inner filter effect; Iron (II) complex; Macrocyclic ligand